2014
DOI: 10.1111/trf.12902
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of anti‐hepatitis B core antigen in hepatitis B virus–vaccinated Chinese blood donors suggests insufficient protection but little threat to the blood supply

Abstract: In an environment of frequent high Genotype B or C viremia, blood donors vaccinated at birth are frequently but mildly infected: asymptomatic and normal alanine aminotransferase level, identified by anti-HBc seroconversion and boosting of anti-HBs. Low viral load and frequent anti-HBs limit transfusion risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(73 citation statements)
references
References 26 publications
12
61
0
Order By: Relevance
“…In 80 initial HBsAg-/DNA+ blood donors, 40% (32/80) were anti-HBs positive and possessed detectable levels of HBV-DNA; of these individuals, eleven, who were followed-up, provided anti-HBs-positive samples, and four had a high viral load. These results were consistent with a study by Zheng et al (26), who showed that of 14 HBV DNA+ vaccinated donors, seven had high levels of anti-HBs. These findings may be explained in part by the findings of Levicnik-Stezinar et al (27), who concluded that low levels of anti-HBs (< 100 IU/L) have limited neutralizing capacity.…”
Section: Discussionsupporting
confidence: 93%
“…In 80 initial HBsAg-/DNA+ blood donors, 40% (32/80) were anti-HBs positive and possessed detectable levels of HBV-DNA; of these individuals, eleven, who were followed-up, provided anti-HBs-positive samples, and four had a high viral load. These results were consistent with a study by Zheng et al (26), who showed that of 14 HBV DNA+ vaccinated donors, seven had high levels of anti-HBs. These findings may be explained in part by the findings of Levicnik-Stezinar et al (27), who concluded that low levels of anti-HBs (< 100 IU/L) have limited neutralizing capacity.…”
Section: Discussionsupporting
confidence: 93%
“…These repeat donors born between 1992 and 1997 were presumably vaccinated for hepatitis B at 0, 1 and 6 months after birth with recombinant vaccines. All blood donors were voluntary and nonremunerated donors and passed the pre‐donation screening for HBsAg and alanine aminotransferase (ALT) . The pre‐qualified donors donated at mobile collection units or at the blood centre.…”
Section: Methodsmentioning
confidence: 99%
“…The pre‐qualified donors donated at mobile collection units or at the blood centre. Blood samples were routinely screened with 2 different EIAs for HBsAg and antibodies to hepatitis C virus (HCV), human immunodeficiency virus types 1 and 2 (HIV1/2), Treponema pallidum (TP) and ALT . Repeat donor samples were further screened with a multiplex NAT for genomes of HBV, HCV and HIV‐1 (Procleix Ultrio; individual‐donation NAT; Grifols Diagnostic Solutions, San Diego, CA; limit of detection [LOD] HBV DNA 10.4 IU/mL).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations